ESTIMATION OF MAGNETIC MATERIAL POTENTIAL USING THE ORDINARY KRIGING METHOD IN SAIRO VILLAGE, MANOKWARI REGENCY, WEST PAPUA PROVINCE: ESTIMASI POTENSI MATERIAL MAGNETIK MENGGUNAKAN METODE ORDINARY KRIGING DI KAMPUNG SAIRO KABUPATEN MANOKWARI PROVINSI PAPUA BARATESTIMASI POTENSI MATERIAL MAGNETIK MENGGUNAKAN METODE ORDINARY KRIGING DI KAMPUNG SAIRO KABUPATEN MANOKWARI PROVINSI PAPUA BARAT - Nababan, Dasdo Rudi Darsono (INTAN Jurnal Penelitian Tambang, 2024)
The calculation of magnetic material resources in the people's mining area in Sairo Village is very important so that the people know the amount of magnetic material in the area. The purpose of this study was to determine the amount of magnetic material and visualize how the distribution of the two materials in the area. The stages carried out to obtain the objectives are sampling, separation of magnetic material, calculating the percentage of magnetic material, statistical analysis, variogram analysis, visualization of resource distribution, ordinary kriging estimation, and resource classification. After calculating and classifying resources, the total resources for magnetic material were inferred = 0 m³, indicated = 24.368 m³, and measured = 74.994 m³.